The I-R system of hybrid dysgenesis in Drosophila melanogaster: Are I factor insertions responsible for the mutator effect of the I-R interaction? - Pelisson, A. (Molecular and General Genetics, 1981)
When Drosophila melanogaster males coming from a class of strains known as inducer are crossed with females from the complementary class (reactive), a quite specific kind of sterile female (SF) is obtained that exhibits other dysgenic traits such as non-disjunctions and non-randomly distributed mutations. This syndrome is caused by the interaction of the 'I factor' linked to inducer chromosomes with the maternally inherited reactive state 'R'. This I--R interaction is also responsible for 'chromosomal contamination' that is likely to result from very frequent I factor insertions into reactive chromosomes. Such insertions might be responsible for the I--R induced mutations and some data concerning this hypothesis are reported here. Out of nine I--R-generated mutants one, the whiteIR1 (wIRI) allele, is closely linked to an I factor, which maps either at the site of the mutation or within less than 0.02 map units. In addition, wIR1 is somewhat unstable when transmitted through SF females. In contrast, the typical I factor does not seem to be associated with any of the eight other mutants as judged by their inability to induce the female sterility characteristic of the I--R syndrome. The possibility is discussed that most of I--R-induced mutations are nevertheless caused by insertions of either undetectable I factors of other transposable elements, not related to I, whose transposition is dependent on the I--R interaction.